Artemisia fiber regenerated composite packaging material and preparation method thereof
Patent Information
- Application Number
- CN202611118017.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-20
AI Technical Summary
艾草植物残余物通常来源于艾草加工过程中的废弃副产物,其形态多呈不规则颗粒或纤维状态,材料本身较为疏松,表面粗糙,在加工过程中容易发生破裂、掉粉等现象,难以直接加工形成具有连续性和柔韧性的片状材料,限制了其在包装材料领域中的应用
本发明以艾草加工过程中产生的艾绒提取渣、艾草精油提取残渣或艾草饮片生产过程中产生的艾草下脚料等植物残余物作为原料,通过预处理、粉碎和筛分处理制备得到艾草颗粒,减少了植物加工副产物的浪费。本发明将艾草颗粒作为再生纤维层的重要组成部分,使所得复合包装材料保留艾草植物来源材料的天然特性。艾草中含有挥发油类、萜类化合物、酚类化合物等天然植物活性成分,使所得材料具有天然植物气味特性。本发明利用艾草材料中天然植物活性组分的特性,使所得复合包装材料具有潜在的抑菌、防异味等功能特性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of environmentally friendly composite materials technology, and in particular to a regenerated Artemisia argyi fiber composite packaging material and its preparation method. Background Technology
[0002] With the continuous development of packaging material applications, composite packaging materials that are lightweight, functional, and processable have attracted widespread attention. Using natural plant resources and agricultural and forestry processing by-products as raw materials to prepare composite materials can improve the utilization efficiency of plant resources and provide new material options for packaging materials.
[0003] Artemisia argyi, a traditional plant resource in my country, generates a large amount of plant residues during the processing of Artemisia argyi floss, extraction of Artemisia argyi essential oil, and production of Artemisia argyi products. Because these plant residues contain a certain proportion of plant fiber, lignin, and natural active ingredients, they have the potential for further development and utilization as raw materials for composite materials.
[0004] Existing technologies include research on the preparation of functional composite materials using Artemisia argyi. For example: Chinese patent application publication number CN105153908A discloses a method for preparing Artemisia argyi coating. This technical solution combines Artemisia argyi powder, waterborne polyurethane, and other additives to prepare Artemisia argyi coating, allowing the Artemisia argyi component to be used as a functional filler in the coating material system. However, this technical solution mainly focuses on the coating system and does not address how to utilize Artemisia argyi plant materials to construct solid composite materials with continuous structures, nor can it meet the requirements of packaging materials for certain mechanical properties and sheet structures.
[0005] Chinese Patent Publication No. CN209629222U discloses a mugwort mattress. This technical solution involves laying and pressing mugwort material at a certain thickness ratio to form a mugwort pad layer, thereby obtaining a breathable mugwort product. However, the mugwort material in this technical solution mainly exists in the form of integral filling or pressing, resulting in a relatively thick structure, which is difficult to further process into a plant-based composite material with controllable thickness, continuous sheet shape, and suitable for the packaging field.
[0006] Chinese patent application publication number CN112323162A discloses a highly efficient sustained-release microcapsule cellulose fiber made from Artemisia argyi. This technical solution involves preparing a fluidized bed of highly efficient sustained-release microcapsules of Artemisia argyi and further preparing a fiber material containing functional components of Artemisia argyi through a spinning process, resulting in fibers with antibacterial properties. However, this technical solution mainly relies on the spinning process, which has high requirements for raw material morphology and processing conditions, and does not involve a method for using Artemisia argyi plant residues to form sheet-like packaging materials by combining them with other natural particulate materials.
[0007] Furthermore, cork, with its naturally porous structure, is lightweight, has good elasticity and resilience, excellent cushioning performance, and good thermal insulation properties, making it well-suited for applications in packaging and protective materials. Therefore, combining Artemisia argyi plant residues with cork holds promise for creating composite packaging materials that combine the characteristics of plant-derived materials with structural properties.
[0008] However, existing technologies still have the following shortcomings: Artemisia plant residues are usually waste byproducts from the processing of Artemisia. They are mostly in the form of irregular particles or fibers. The material itself is relatively loose and has a rough surface. During processing, it is prone to cracking and powdering, making it difficult to directly process into sheet materials with continuity and flexibility, which limits its application in the field of packaging materials.
[0009] Plant particle composites typically rely on adhesives to bond the particles together. However, due to differences in the surface structure, hygroscopic properties, and chemical composition of plant particles, the interfacial bonding stability between particles and adhesives is limited. Under long-term use or humid conditions, interfacial damage can easily occur, leading to a decline in the mechanical properties and structural stability of the material.
[0010] Most existing plant-based composite materials are made into thick structures by particle pressing or sheet molding. Although they can achieve a certain overall strength, the material thickness is large and the flexibility is insufficient, making it difficult to further process them into lightweight, flexible packaging materials that can be bent, folded, and suitable for sewing and other processes.
[0011] Therefore, it is still necessary to develop a new plant-based composite packaging material and its preparation method. By rationally constructing a plant particle composite system, the problems of easy breakage and difficult processing of Artemisia argyi plant residues can be improved. Combined with sheet forming and thinning processes, a continuous sheet structure can be formed. At the same time, the interfacial bonding stability between plant particles and adhesives can be improved, thereby obtaining a regenerated Artemisia argyi fiber composite packaging material that combines the characteristics of plant-based materials, structural stability, flexible processing performance, and packaging applicability. Summary of the Invention
[0012] In view of the above-mentioned deficiencies of the prior art, the technical problem to be solved by the present invention is to provide a regenerated Artemisia argyi fiber composite packaging material and its preparation method.
[0013] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A regenerated Artemisia fiber composite packaging material includes a regenerated fiber layer and a flexible fabric layer compositely connected to the regenerated fiber layer. The regenerated fiber layer is a continuous sheet-like composite layer formed by consolidation of Artemisia argyi particles, cork particles and an adhesive system. The regenerated fiber layer is prepared by the following method: Artemisia argyi granules and cork granules are mixed with an adhesive system to obtain a composite granule mixture; The composite particle mixture is laid to form a composite particle blank; The composite particle preform is pressed and cured to form a recycled fiber board; The recycled fiber board is thinned to obtain the recycled fiber layer.
[0014] Furthermore, the flexible fabric layer is either polyester or polyurethane fabric. The polyester fabric has a unit area mass of 70-90 g / m². The polyurethane fabric is a polyurethane-coated fabric with a unit area mass of 250-350 g / m².
[0015] Further, the mugwort granules are obtained from mugwort through pretreatment, crushing, and sieving. Even further, the mugwort granules are obtained from mugwort plant residue through pretreatment, crushing, and sieving. The mugwort plant residue is mugwort floss extraction residue produced during mugwort floss extraction, residue after mugwort essential oil extraction, or mugwort by-products produced during the production of mugwort slices. Preferably, the average particle size of the mugwort granules is 0.5-3.0 mm. Preferably, the moisture content of the mugwort granules is 10-14%.
[0016] Furthermore, the cork particles are obtained from cork plant material through pretreatment, crushing, drying, and sieving. The cork plant material is selected from one or more of cork oak bark, oak bark, or other woody materials that can be used to prepare cork particles, preferably cork oak (Quercus suber) bark. Preferably, the average particle size of the cork particles is 1.0-3.0 mm, and the moisture content is 6-9%.
[0017] The adhesive system is used to form a stable bond between the Artemisia argyi particles and the cork particles, and to form a continuous composite structure after curing. Further, the adhesive system can be selected from waterborne polyurethane adhesives, acrylic adhesives, or other adhesives suitable for flexible composite materials, preferably waterborne polyurethane adhesives. The waterborne polyurethane adhesive may be a commercially available waterborne polyurethane adhesive, and exemplary, may include, but is not limited to, Dispercoll® U2824, Dispercoll® U XP 2643, Dispercoll® U 2710, Dispercoll® U 2662, HYDRAN® WLS-201, HYDRAN® WLS-210, HYDRAN® WLA-515AR, HYDRAN® WLA-535AR, Sancure™ 20899, Sancure™ 861, Sancure™ 942, ALBERDINGK® U 410, ALBERDINGK® U 5201, ALBERDINGK® U 6300, ALBERDINGK® U 801, or ALBERDINGK® U 9900. Preferably, the waterborne polyurethane adhesive is Dispercoll® U 2824, Dispercoll® U XP 2643, HYDRAN® WLA-515AR, or Sancure™ 861.
[0018] Furthermore, the adhesive system may also contain interfacial reinforcing agents, crosslinking reinforcing agents, mildew inhibitors, or other functional additives to improve the interfacial bonding performance, water resistance, or environmental stability of the composite material.
[0019] Furthermore, the adhesive system further includes a silane coupling agent. The amount of the silane coupling agent added is 0.5-5% of the mass of the adhesive system. Preferably, it is 1-3%. Preferably, the silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane (KH-550), γ-glycidoxypropyltrimethoxysilane (KH-560), γ-methacryloyloxypropyltrimethoxysilane (KH-570), and N-β(aminoethyl)-γ-aminopropyltrimethoxysilane (KH-792).
[0020] Furthermore, the adhesive system further includes polycarbodiimide. The amount of polycarbodiimide added is 0.5-5% of the mass of the adhesive system. Preferably, it is 1-3%. The polycarbodiimide can be selected from water-based polycarbodiimide crosslinking agents. Preferably, the polycarbodiimide is CARBODILITE® V-02-L2 or Picassian® XL-702. Most preferably, the polycarbodiimide is CARBODILITE® V-02-L2.
[0021] Further, the adhesive system comprises a waterborne polyurethane adhesive, a silane coupling agent, and polycarbodiimide. The amount of silane coupling agent added is 0.25-2.5% of the mass of the adhesive system, and the amount of polycarbodiimide added is 0.25-2.5% of the mass of the adhesive system. Preferably, the amount of silane coupling agent added is 0.5-1.5% of the mass of the adhesive system, and the amount of polycarbodiimide added is 0.5-1.5% of the mass of the adhesive system. The silane coupling agent is KH-550, and the polycarbodiimide is CARBODILITE® V-02-L2.
[0022] Furthermore, the composite particle mixture is composed of 10-30 parts by weight of Artemisia argyi particles, 20-40 parts by weight of cork particles, and 1-6 parts by weight of an adhesive system.
[0023] Furthermore, the composite particle mixture is laid in a mold to form a composite particle blank with a thickness of 5-30cm.
[0024] Furthermore, the pressing and curing process includes pressing and molding and heating and curing; wherein, the pressing and molding process is used to compact the composite particle blank, and the heating and curing process is used to cure the adhesive, so that a stable bond structure is formed between the artemisia particles and the cork particles.
[0025] Furthermore, the pressing and molding process is a cold pressing and molding process.
[0026] Furthermore, the cold pressing process is performed at a pressure of 1-5 MPa for a time of 5-20 min.
[0027] Furthermore, the temperature of the heat curing treatment is 100-150℃, and the time is 10-60 min.
[0028] Furthermore, the recycled fiber board formed by the pressing and curing process is mechanically thinned by slitting, planing or cutting along the thickness direction, so that the recycled fiber board forms a continuous sheet-like recycled fiber layer.
[0029] Furthermore, the thickness of the regenerated fiber layer is 0.1-1.0 mm, preferably 0.2-0.3 mm.
[0030] Furthermore, the regenerated fiber layer and the flexible fabric layer are compositely connected by a hot-press bonding method.
[0031] Furthermore, the hot-pressing bonding temperature is 100-140℃, the pressure is 0.3-0.8MPa, and the time is 30-180s.
[0032] Furthermore, the present invention also provides a method for preparing the above-mentioned Artemisia argyi fiber recycled composite packaging material, comprising the following steps: S1. Preparation of particulate raw materials: Artemisia argyi plant residue is pretreated, crushed and sieved to obtain Artemisia argyi granules; Cork plant materials are pretreated, crushed, dried and sieved to obtain cork particles; S2. Preparation of composite particle mixture: After premixing the artemisia argyi granules and cork granules, an adhesive is added and the mixture is continued to be mixed evenly to obtain a composite granule mixture. S3. Formation of composite particle green body: The composite particle mixture is laid in a mold to form a composite particle preform with a predetermined thickness; S4, Preparation of recycled fiber board: The composite particle blank is pressed and molded to form a preformed plate. The preformed board is then subjected to heat curing treatment to cure the adhesive, thereby obtaining a recycled fiber board. S5. Preparation of regenerated fiber layer: The recycled fiber board is mechanically thinned along the thickness direction to obtain a continuous sheet-like recycled fiber layer; S6. Preparation of composite packaging materials: The regenerated fiber layer and the flexible fabric layer are thermally bonded together to form a composite connection between the regenerated fiber layer and the flexible fabric layer, thereby obtaining the Artemisia argyi fiber regenerated composite packaging material.
[0033] Further, in step S2, the weight ratio of the mugwort granules, cork granules and adhesive is (10-30):(20-40):(1-6).
[0034] Furthermore, the composite particle mixture described in step S3 is laid in a mold to form a composite particle blank with a thickness of 5-30cm.
[0035] Furthermore, the pressing process described in step S4 is a cold pressing process.
[0036] Furthermore, the cold pressing process in step S4 is performed at a pressure of 1-5 MPa for a time of 5-20 min.
[0037] Furthermore, the heating and curing treatment in step S4 is performed at a temperature of 100-150°C for a time of 10-60 minutes.
[0038] Furthermore, the mechanical thinning process described in step S5 includes slitting, planing, or cutting.
[0039] Furthermore, in step S6, the heat bonding temperature is 100-140℃, the pressure is 0.3-0.8MPa, and the time is 30-180s.
[0040] Compared with the prior art, the present invention has the following beneficial effects: This invention uses plant residues such as mugwort floss extraction residue, mugwort essential oil extraction residue, or mugwort by-products from the production of mugwort slices as raw materials. Through pretreatment, crushing, and sieving, mugwort granules are prepared, reducing the waste of plant processing by-products. This invention incorporates mugwort granules as an important component of the regenerated fiber layer, allowing the resulting composite packaging material to retain the natural characteristics of the mugwort plant-derived material. Mugwort contains volatile oils, terpenoids, phenolic compounds, and other natural plant active ingredients, giving the resulting material a natural plant aroma. This invention utilizes the characteristics of the natural plant active components in mugwort materials to give the resulting composite packaging material potential antibacterial and odor-resistant functional properties.
[0041] This invention uses cork particles as a composite component. Cork material is derived from cork plants such as the cork oak, and its interior has a rich honeycomb cell structure, characterized by its light weight, good elasticity and resilience, excellent cushioning performance, and good thermal insulation properties. Combining cork particles with artemisia particles helps reduce the overall density of the material, improving its cushioning performance and packaging suitability.
[0042] This invention uses artemisia argyi granules, cork granules and adhesives to form a composite granular mixture, and then lays it into a blank and presses it to cure it to form a recycled fiber board. This transforms the plant materials, which were originally in a discrete granular state, into a composite material with a continuous structure, thereby improving the bonding stability between plant particles and the overall integrity of the material.
[0043] This invention employs a process route of granular composite molding, sheet preparation, and thinning treatment to transform plant granular materials, which are traditionally difficult to process directly into continuous sheets, into continuous sheet-like regenerated fiber layers. This solves the problem that existing plant granular materials are difficult to form thin, continuous structures and improves the processing adaptability of plant-based composite materials.
[0044] This invention obtains a thin, continuous sheet-like layer of regenerated fiber by thinning the regenerated fiber board, and further combines it with a flexible fabric layer, so that the resulting material has both the natural properties of plant-based materials and the processing performance of flexible fabrics.
[0045] This invention uses an adhesive suitable for plant particle composite systems to form a stable bond between Artemisia argyi particles and cork particles, and to form a continuous composite layer after curing, which helps to improve the structural integrity and stability of the material.
[0046] The preparation method of this invention has a simple process route and a wide range of raw material sources. It can utilize the by-products of Artemisia argyi processing and natural cork resources to prepare environmentally friendly composite packaging materials, thereby realizing the recycling of plant resources.
[0047] Furthermore, by optimizing the adhesive system, the interfacial bonding performance between Artemisia argyi granules, cork granules and adhesives can be further improved; by introducing modified components such as silane coupling agents and polycarbodiimide, the interfacial bonding ability between plant granules and adhesives and the water resistance stability of the adhesive curing system can be enhanced, thereby improving the interlayer bonding strength, performance retention after immersion and long-term stability of the composite packaging material. Attached Figure Description
[0048] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0049] Figure 1 This is a process diagram for preparing Artemisia argyi fiber recycled composite packaging material.
[0050] Figure 2 This is a photograph of the Artemisia argyi fiber recycled composite packaging material prepared in Example 1. Detailed Implementation
[0051] The invention will be more readily understood by referring to the following detailed description of preferred embodiments and included examples. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In case of conflict, the definitions in this specification shall prevail.
[0052] 1. Preparation of Artemisia argyi granules Artemisia flakes extraction residue from Artemisia argyi produced in Nanyang, Henan Province, was used as raw material. The Artemisia flakes extraction residue was pressed and dehydrated, and then dried to obtain dried Artemisia argyi residue. The dried Artemisia argyi residue was then crushed and sieved to obtain Artemisia argyi particles with an average particle size of 1.1 mm and a moisture content of 11.9%, which were then set aside for use.
[0053] 2. Preparation of Cork Particles Corkwood (Quercus suber) supplied by Francisco Oller SA was used as raw material. It was crushed, dried and sieved in sequence to obtain cork particles with an average particle size of 1.5 mm and a moisture content of 7.4%, which were then set aside for use.
[0054] Unless otherwise stated, all the following examples and comparative examples use the same batch of Artemisia argyi granules and cork granules prepared above to ensure that the source of raw materials, particle size and moisture content are consistent, and to reduce the impact of raw material differences on the test results.
[0055] Unless otherwise specified, the flexible fabric layers used in the following examples and comparative examples are all polyester fabrics with a unit area mass of 80 g / m². The silane coupling agents used are γ-aminopropyltriethoxysilane (KH-550) and Dow Corning Z-6011.
[0056] Example 1 The preparation method and process steps of the Artemisia argyi fiber recycled composite packaging material are described in [link to relevant documentation]. Figure 1 .
[0057] 20 parts by weight of Artemisia argyi granules and 30 parts by weight of cork granules were mixed with 2 parts by weight of Dispercoll® U 2824 waterborne polyurethane adhesive to obtain a composite granule mixture. The composite granule mixture is evenly spread in a mold with dimensions of 60cm×135cm, and the spreading thickness is controlled to be 15cm to form a composite granule blank. The composite particle blank is placed in a cold pressing device and cold-pressed at a pressure of 2.5MPa for about 10 minutes to compact the composite particle blank into a preformed board with a thickness of 10cm; the preformed board is then subjected to a heat curing treatment at 130℃ for 30 minutes to cure the adhesive and obtain a recycled fiber board. The recycled fiber board is cut along the thickness direction to obtain a thin sheet with a thickness of 0.25 mm. The recycled fiber layer is obtained through the above-mentioned thinning process. After the regenerated fiber layer is laminated with the polyester fabric, it is hot-pressed at 120°C and 0.5MPa for 90 seconds to achieve a composite connection between the regenerated fiber layer and the polyester fabric. The exposed surface of the regenerated fiber layer is then sanded using a 600-mesh sandpaper to remove 0.02mm of material, removing protruding plant particles and fiber burrs, resulting in a smooth and flat surface. This yields the Artemisia argyi fiber regenerated composite packaging material. Figure 2 As shown.
[0058] Comparative Example 1 Except for the raw material system, the rest of the preparation process is the same as in Example 1.
[0059] Specifically, 50 parts by weight of Artemisia argyi granules are mixed with 2 parts by weight of Dispercoll® U 2824 waterborne polyurethane adhesive to obtain a composite granule mixture.
[0060] Subsequently, the composite particle mixture is evenly spread in a mold with dimensions of 60cm×135cm, and the spreading thickness is controlled to be 15cm to form a composite particle blank. The composite particle blank is placed in a cold pressing device and cold-pressed at a pressure of 2.5MPa for about 10 minutes to compact and shape the composite particle blank, thereby obtaining a pre-formed board with a thickness of 10cm. The pre-formed board is then subjected to a heat curing treatment at 130℃ for 30 minutes to cure the adhesive, thereby obtaining a recycled fiber board.
[0061] The recycled fiber board is cut along its thickness to obtain a sheet with a thickness of 0.25 mm. The recycled fiber layer is obtained through the above-mentioned thinning treatment. The recycled fiber layer is then stacked with the polyester fabric and hot-pressed at 120°C and 0.5 MPa for 90 seconds to achieve a composite connection between the recycled fiber layer and the polyester fabric. The exposed surface of the recycled fiber layer is sanded and finished using a 600-mesh sanding belt to remove 0.02 mm of thickness, remove protruding plant particles and fiber burrs from the surface, and make the exposed surface of the recycled fiber layer smooth and flat, thus obtaining the composite packaging material of Comparative Example 1.
[0062] Comparative Example 2 Except for not performing the thinning treatment of recycled fiber boards, the raw materials and preparation process are the same as in Example 1.
[0063] Specifically, 20 parts by weight of Artemisia argyi granules, 30 parts by weight of cork granules, and 2 parts by weight of Dispercoll® U2824 waterborne polyurethane adhesive are mixed to obtain a composite granule mixture.
[0064] Subsequently, the composite particle mixture is evenly spread in a mold with dimensions of 60cm×135cm, and the spreading thickness is controlled to be 15cm to form a composite particle blank. The composite particle blank is placed in a cold pressing device and cold-pressed at a pressure of 2.5MPa for about 10 minutes to compact and shape the composite particle blank, thereby obtaining a pre-formed board with a thickness of 10cm. The pre-formed board is then subjected to a heat curing treatment at 130℃ for 30 minutes to cure the adhesive, thereby obtaining a recycled fiber board.
[0065] The recycled fiber board was used directly as a composite layer without mechanical thinning. After being stacked with the polyester fabric, it was hot-pressed at 120°C and 0.5MPa for 90 seconds to bond the recycled fiber board and the polyester fabric together. The exposed surface of the recycled fiber board was sanded and finished with a 600-mesh sanding belt to remove 0.02mm of thickness, remove protruding plant particles and fiber burrs, and make the exposed surface of the composite layer smooth and flat, thus obtaining the composite packaging material of Comparative Example 2.
[0066] Observations revealed that the composite packaging material obtained in Comparative Example 2 had a larger overall thickness and higher bending stiffness, resulting in significant resistance during bending and making it impossible to meet the folding and rolling processing requirements of flexible packaging materials.
[0067] Comparative Example 3 Except for the molding process, the other raw materials and preparation processes are the same as in Example 1.
[0068] Specifically, 20 parts by weight of Artemisia argyi granules, 30 parts by weight of cork granules, and 2 parts by weight of Dispercoll® U2824 waterborne polyurethane adhesive are mixed to obtain a composite granule mixture.
[0069] Subsequently, the composite particle mixture is evenly spread in a mold with a size of 60cm×135cm to form a composite particle paving layer.
[0070] Instead of cold-pressing and heat-curing the composite particle layer to form a recycled fiber board, the composite particle layer is directly laminated with the polyester fabric and hot-pressed at 120°C and 0.5MPa for 90 seconds to bond the composite particle layer with the polyester fabric.
[0071] Subsequently, the exposed surface of the composite particle layer was sanded and finished using a 600-mesh abrasive belt to remove protruding plant particles and fiber burrs, and the thickness of the resulting composite packaging material was controlled to 0.23 mm.
[0072] Example 2 Except for the adhesive system, the other raw materials and preparation process are the same as in Example 1.
[0073] Specifically, 20 parts by weight of Artemisia argyi granules and 30 parts by weight of cork granules are mixed with 2 parts by weight of modified adhesive to obtain a composite granular mixture. The modified adhesive consists of Dispercoll® U 2824 waterborne polyurethane adhesive and silane coupling agent KH-550, with the amount of silane coupling agent added being 2.0% of the mass of the modified adhesive.
[0074] Subsequently, the Artemisia argyi fiber recycled composite packaging material was prepared according to the laying, cold pressing, heating and curing, thinning and heat bonding processes in Example 1.
[0075] Example 3 Except for the adhesive system, the other raw materials and preparation process are the same as in Example 1.
[0076] Specifically, 20 parts by weight of Artemisia argyi granules and 30 parts by weight of cork granules are mixed with 2 parts by weight of modified adhesive to obtain a composite granular mixture. The modified adhesive consists of Dispercoll® U 2824 waterborne polyurethane adhesive and polycarbodiimide CARBODILITE® V-02-L2, with the amount of polycarbodiimide added being 2.0% of the mass of the modified adhesive.
[0077] Subsequently, the Artemisia argyi fiber recycled composite packaging material was prepared according to the laying, cold pressing, heating and curing, thinning and heat bonding processes in Example 1.
[0078] Example 4 Except for the adhesive system, the other raw materials and preparation process are the same as in Example 1.
[0079] Specifically, 20 parts by weight of Artemisia argyi granules and 30 parts by weight of cork granules are mixed with 2 parts by weight of modified adhesive to obtain a composite granular mixture. The modified adhesive consists of Dispercoll® U 2824 waterborne polyurethane adhesive, silane coupling agent KH-550, and polycarbodiimide CARBODILITE® V-02-L2. The amount of silane coupling agent added is 1.0% of the mass of the modified adhesive, and the amount of polycarbodiimide added is 1.0% of the mass of the modified adhesive.
[0080] Subsequently, the Artemisia argyi fiber recycled composite packaging material was prepared according to the laying, cold pressing, heating and curing, thinning and heat bonding processes in Example 1.
[0081] Example 5 The difference from Example 4 is that the amount of silane coupling agent added is 0.5% of the mass of the modified adhesive, and the amount of polycarbodiimide added is 1.5% of the mass of the modified adhesive.
[0082] Example 6 The difference from Example 4 is that the amount of silane coupling agent added is 1.5% of the mass of the modified adhesive, and the amount of polycarbodiimide added is 0.5% of the mass of the modified adhesive.
[0083] Example 7 The difference from Example 3 is that CARBODILITE® V-02-L2 is replaced with an equal amount of Picassian® XL-702.
[0084] Example 8 The difference from Example 4 is that CARBODILITE® V-02-L2 is replaced with an equal amount of Picassian® XL-702.
[0085] Test example: To evaluate the effects of different adhesive systems on the interlayer bonding performance and wet environment stability of the Artemisia argyi fiber recycled composite packaging material, the interlayer peel strength of the Artemisia argyi fiber recycled composite packaging materials prepared in the examples and comparative examples was tested.
[0086] The test was conducted in accordance with the method specified in GB / T 2790-1995 "Test method for 180° peel strength of adhesives - flexible materials vs. rigid materials".
[0087] Artemisia fiber recycled composite packaging material was cut into strips with a width of 25 mm and a length of 200 mm, and 5 parallel samples were prepared for each group of samples.
[0088] Before testing, the sample was placed in an environment with a temperature of 23±2℃ and a relative humidity of 50±5% for 24 hours to allow it to reach a stable state.
[0089] During testing, the regenerated fiber layer and polyester fabric layer at one end of the sample are pre-peeled. The polyester fabric layer is fixed in the upper fixture of the electronic universal testing machine as a flexible peeling layer, and the regenerated fiber layer is fixed in the lower fixture, so that the peeling direction is kept at 180°.
[0090] Continuous peel tests were conducted using an electronic universal testing machine with a peel speed of 100±10 mm / min. The peel force variation curve during the peel process was recorded, and the average peel force F0 in the stable peel stage was taken. The interlayer peel strength P0 before immersion treatment was calculated according to the following formula.
[0091] Interlayer peel strength is calculated using the following formula: P=F / b Where: P is the interlayer peel strength, in N / 25mm; F is the average peel force during the stable peel stage, in N; b is the sample width, in 25mm.
[0092] Subsequently, another sample from the same batch was completely immersed in deionized water and soaked at 25°C for 24 hours.
[0093] After the immersion treatment, the sample was removed, the surface moisture was absorbed with filter paper, and the sample was left to stand for 30 minutes at an environment with a temperature of 23±2℃ and a relative humidity of 50±5%.
[0094] The test was then conducted according to the 180° peel test method described above, and the average peel force F1 in the stable peel stage was obtained. The interlayer peel strength P1 after water immersion treatment was calculated according to the above formula.
[0095] The interlayer peel strength retention rate after immersion in water is calculated according to the following formula: R = P1 / P0 × 100% Where: R is the interlayer peel strength retention rate after immersion in water; P0 is the interlayer peel strength before immersion in water; P1 is the interlayer peel strength after immersion in water.
[0096] The test results are shown in Table 1 below.
[0097] Table 1: Test results of interlayer peel strength and retention rate of composite packaging materials before and after immersion in water.
[0098] Compared to Example 1, Comparative Example 1, which did not include cork particles and only used Artemisia argyi particles and adhesives to prepare the regenerated fiber layer, showed significantly reduced interlayer peel strength and water retention. This indicates that the introduction of cork particles not only improves the structural integrity of the composite material as a plant-based filler but also forms a multi-scale particle packing structure with Artemisia argyi particles, increasing the contact area between particles and the uniformity of adhesive distribution among particles, thereby enhancing the internal bonding stability of the regenerated fiber layer. Furthermore, cork particles possess a certain degree of elasticity and porous structure, which can improve the internal stress distribution of the composite material and reduce interfacial damage caused by the hygroscopic expansion of plant particles during water immersion. Therefore, the plant particle system composed of Artemisia argyi particles and cork particles is key to improving the interlayer bonding performance and wet environment stability of composite packaging materials.
[0099] Compared to Example 1, Comparative Example 3 did not undergo pressing and curing to form a recycled fiber board. Instead, the composite particle mixture was directly bonded to the flexible fabric layer, resulting in significantly reduced interlayer peel strength and water retention. This indicates that relying solely on adhesives to connect plant particles to the flexible fabric is insufficient to form a stable and continuous plant-based composite structure. The pressing process allows the Artemisia argyi and cork particles to form a dense spatial arrangement, promoting thorough wetting and curing of the adhesive between the particles, resulting in a continuous sheet-like recycled fiber layer with overall load-bearing capacity. Simultaneously, the cured continuous structure effectively restricts the displacement and interfacial detachment of plant particles after moisture absorption, improving the structural stability of the material under humid conditions.
[0100] Compared with Example 1, Example 2 showed that after modifying the waterborne polyurethane adhesive system with a silane coupling agent, the interlayer peel strength and water retention rate of the material were improved. This indicates that the silane coupling agent can enhance the interfacial bonding performance between plant particles and adhesives and improve the stability of the material in a wet environment.
[0101] In Example 3, after modification with polycarbodiimide CARBODILITE® V-02-L2, the interlayer peel strength retention rate of the material after immersion in water was further improved, indicating that polycarbodiimide CARBODILITE® V-02-L2 can improve the water resistance stability of the waterborne polyurethane adhesive curing system and reduce the material performance degradation under immersion conditions.
[0102] Examples 4-6 show that after modification with a silane coupling agent and polycarbodiimide CARBODILITE® V-02-L2, the interlayer bonding performance and water immersion stability of the materials were further improved, indicating that the two agents exert a synergistic effect by enhancing the interfacial bonding of plant particles / adhesive and improving the stability of the adhesive curing system, respectively. By optimizing the addition ratio of the two agents, the overall performance of the composite packaging material can be further improved.
[0103] This invention uses Artemisia argyi plant residue and cork material as raw materials, and prepares a composite packaging material with a continuous sheet structure through particle composite, sheet forming and thinning processes. This improves the problem that plant particle materials are difficult to directly process into flexible thin-layer materials, so that the resulting material has both the characteristics of plant-based materials and the processing performance required for flexible packaging materials.
[0104] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions conceived without inventive effort should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope defined in the claims.
Claims
1. A composite packaging material made from recycled Artemisia argyi fiber, characterized in that, It includes a regenerated fiber layer and a flexible fabric layer compositely connected to the regenerated fiber layer; The regenerated fiber layer is a continuous sheet-like composite layer formed by consolidation of Artemisia argyi particles, cork particles and an adhesive system. The regenerated fiber layer is prepared by a method comprising the following steps: Artemisia argyi granules and cork granules are mixed with an adhesive system to obtain a composite granule mixture; The composite particle mixture is laid to form a composite particle blank; The composite particle preform is pressed and cured to form a recycled fiber board. The recycled fiber board is thinned to obtain the recycled fiber layer; The regenerated fiber layer is combined with the flexible fabric layer to obtain the Artemisia argyi fiber regenerated composite packaging material.
2. The Artemisia argyi fiber recycled composite packaging material according to claim 1, characterized in that, The flexible fabric layer is made of polyester or polyurethane.
3. The Artemisia argyi fiber recycled composite packaging material according to claim 1, characterized in that, The mugwort granules are prepared from mugwort plant residue through pretreatment, crushing and sieving. The mugwort plant residue is selected from one or more of the following: mugwort floss extraction residue produced during the mugwort floss extraction process, residue after mugwort essential oil extraction, or mugwort by-products produced during the production of mugwort slices.
4. The Artemisia argyi fiber recycled composite packaging material according to claim 3, characterized in that, The average particle size of the mugwort granules is 0.5-3.0 mm, and the moisture content is 10-14%.
5. The Artemisia argyi fiber recycled composite packaging material according to claim 1, characterized in that, The cork granules are obtained from cork plant materials through pretreatment, crushing, drying and sieving. The cork plant material is selected from one or more of the following: cork oak bark, bark of other oak species, or woody materials that can be used to prepare cork pellets.
6. The Artemisia argyi fiber recycled composite packaging material according to claim 5, characterized in that, The cork particles have an average particle size of 1.0-3.0 mm and a moisture content of 6-9%.
7. The Artemisia argyi fiber recycled composite packaging material according to claim 1, characterized in that, The adhesive system is selected from one or more of waterborne polyurethane adhesives and acrylic adhesives.
8. A method for preparing a regenerated Artemisia argyi fiber composite packaging material according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Artemisia argyi plant residue is used to prepare Artemisia argyi granules, and cork plant material is used to prepare cork granules. S2. Mix the mugwort granules, cork granules and adhesive system evenly to obtain a composite granule mixture; S3. The composite particle mixture is laid to form a composite particle blank; S4. The composite particle blank is pressed and molded, and then heated and cured to obtain recycled fiber board. S5. The regenerated fiber board is mechanically thinned to obtain a regenerated fiber layer with a continuous sheet structure; S6. The regenerated fiber layer and the flexible fabric layer are thermally bonded together to obtain the Artemisia argyi fiber regenerated composite packaging material.
9. The preparation method according to claim 8, characterized in that, The composite particle mixture is formed by mixing 10-30 parts by weight of Artemisia argyi particles, 20-40 parts by weight of cork particles and 1-6 parts by weight of adhesive system; The pressing and molding process is a cold pressing process, with a pressure of 1-5 MPa and a time of 5-20 min; The heating and curing process is carried out at a temperature of 100-150℃ for 10-60 minutes.
10. The preparation method according to claim 8, characterized in that, The mechanical thinning process includes slitting, planing, or cutting. The heat bonding temperature is 100-140℃, the pressure is 0.3-0.8MPa, and the time is 30-180s.
Citation Information
Patent Citations
Preparation method of wormwood paint
CN105153908A
Efficient slow-release wormwood microencapsulation cellulose fiber
CN112323162A
Wormwood mattress
CN209629222U